Returning to simple foreign adoption: commentary on the RGDRN of 16 November 2018 (30th) - Sánchez Cano, Mª Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The effects of a simple foreign adoption are not restricted to the establishment of a parental filiation link and parental responsibility, but also generate other consequences associated with the adoptive filiation, such as the regime of the name and surname of the adoptee in simple form. This is the case of the RGDRN (30th) of 16 November 2018, which analyses the validity of a simple French adoption in the context of a file on a change of name and surname.
Keywords: simple adoption; name and surname; international adoption